2015
DOI: 10.1007/s10710-015-9252-6
|View full text |Cite
|
Sign up to set email alerts
|

Progress properties and fitness bounds for geometric semantic search operators

Abstract: Metrics are essential for geometric semantic genetic programming. On one hand, they structure the semantic space and govern the behavior of geometric search operators; on the other, they determine how fitness is calculated. The interactions between these two types of metrics are an important aspect that to date was largely neglected. In this paper, we investigate these interactions and analyze their consequences. We provide a systematic theoretical analysis of the properties of abstract geometric semantic sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In [15], the importance of metrics for GSGP was discussed. According to the authors, two main types of metrics can be identified: measures that structure the semantic space and govern the behavior of geometric search operators and metrics that determine how fitness is calculated.…”
Section: Previous and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], the importance of metrics for GSGP was discussed. According to the authors, two main types of metrics can be identified: measures that structure the semantic space and govern the behavior of geometric search operators and metrics that determine how fitness is calculated.…”
Section: Previous and Related Workmentioning
confidence: 99%
“…According to the authors, two main types of metrics can be identified: measures that structure the semantic space and govern the behavior of geometric search operators and metrics that determine how fitness is calculated. The first kind of metrics is clearly very important for the work presented here, while for the second kind of metric, this work differs from [15] given that no type of error between calculated values and targets is used here to assess the quality of the evolving individuals. An idea that can be considered as orthogonal to the one of the alignment in the error space is the one presented in [16], where a new type of crossover called subtree semantic geometric crossover (SSGC) was proposed.…”
Section: Previous and Related Workmentioning
confidence: 99%
“…e motivation for choosing GSX E over GSX M for GSGP-Red comes from the fact that GSX M multiplies the parents by a randomly generated function-contrary to the linear combination performed by GSX E -which would imply in additional complexity in time and space to store and manipulate a function instead of a constant. Notice that the usage of the GSX E over the GSX M or vice versa is an open discussion in the literature, with some works defending the usage of GSX M , given empirical analysis [16], and others defending the usage of GSX E , given its progression properties [21].…”
Section: Gsgp-redmentioning
confidence: 99%